Associations of maternal and neonatal serum trace element concentrations with neonatal birth weight. - Shinya Tsuzuki (Public Library of Science (PLoS), 2013)
Background Trace elements play important nutritional roles in neonates. Our objective was to examine whether there are differences in maternal/neonatal serum trace element concentrations between mature infants and premature infants. Methods During 2012, 44 infants born at National Center for Global Health and Medicine, Tokyo, Japan, were enrolled. Serum samples were collected to measure serum iron, zinc, copper, and selenium concentrations 5 days after birth. Maternal serum samples were obtained before delivery and cord blood was taken at delivery to measure the same trace elements. We compared the results between term group whose birth weight were ≥2500 g and gestational age were ≥37 weeks and premature group whose birth weight were <2500 g or gestational age were <37 weeks. Variables significantly different between two groups were included in linear regression models to identify significant predictors of birth weight. Values of P<0.05 were considered statistically significant. Results Serum selenium concentrations were lower in premature group than in term group (43.3±7.0 µg/L vs. 52.0±8.9 µg/L, P = 0.001). Maternal serum selenium concentrations were also significantly lower in the mothers of premature group than in the mothers of term group (79.3±19.3 µg/L vs. 94.1±18.1 µg/L, P = 0.032). There were no significant differences in neonatal or maternal iron, zinc, or copper concentrations between two groups. Multivariate linear regression analysis showed that, except for gestational age, only maternal serum selenium was significantly associated with birth weight (P = 0.015). Conclusions Serum selenium concentrations were lower in premature group and their mothers compared with the term group. The maternal serum selenium concentration was positively correlated with birth weight. These results suggest that maternal serum selenium concentration may influence neonatal birth weight.